Práticas autogestionárias em uma sociedade heterogestionária : contribuições da formação em economia solidária - Moraes, Rochele Pedroso de (2020)
This Thesis seeks to problematize the contradictions that exist in self-management practices, in a society that is predominantly hetero-management, with the contribution of training in Solidarity Economy. We seek to understand how self-management practices occurin the field of work in Solidarity Economy, and its formative process, inserted in the neoliberal context. For this, we developed a qualitative theoretical research, bibliographic research and example analysis, using documentary analysis, in electronic source. To support our knowledge construction, we refer to Historical Materialism. The reference authors were Antonio David Cattani, Christian Laval, David Harvey, Gaudêncio Frigoto, Karl Marx, Marcio Pochmann, Marilda Vilela Iamamoto, Moacyr Gadotti, Paul Singer, Paulo Freire, Pierre Dardot, Potyara Pereira Amazoneida, Ricardo Antunes, among others. The research problem was: How is it possible to think about self-management practices in a society with a predominance of hetero-management practices? In the objective we intend: To problematize about the practices of self-management, the formation in Solidarity Economy, opposite to the practices of hetero-management, which characterize neoliberal society. In the specific objectives: Demonstrate what are the contradictions in facing self-management practices in the Solidarity Economy in a heterogestionary society and identify how the formations in the field of work are configured in the perspective of the Solidarity Economy. The supporting material, for example analysis in the research, was the electronic document: The public policy of Education in Solidarity Economy through CFES Sul, result of the systematization of the formation process in Solidarity Economy, presented by the institution Camp, on the execution ofthe Project CFES sul, in the years 2014 and 2015. As a result of the analyzes, we found that it is possible to materialize self-managed practices, in the context of a hetero-managed neoliberal society. The training in Solidarity Economy brings elements related to the productive chain, commercialization and the realization of consumption, as well as the constitution of a production and credit cooperation network. It is a contradictory process by nature, which requires a lot of resistance and learning in thecommunity.